Implantação de sistemas ERP: tecnologia e pessoas no projeto Garoto-SAP - Jesus, Renata Gomes (2004)
As verifies the advance of the Information Technology, there is an increase in the number of companies that adopt computational systems to assist in their activities. In the 90’s, the use of systems ERP package (acronym to Enterp